Launch and impact characteristics of typical multi-layered flyers driven by ns-pulsed laser. (December 2019) - Zhang, Haonan; Wu, Lizhi; Hu, Peng; Guo, Wei; Zhang, Wei; Ye, Yinghua; Shen, Ruiqi
Highlights: How various materials influenced flyers' launch and impact properties was dissected. The ablation of K9 substrate weakened the kinetic energy coupling when driving flyer. Appearances of the PMMA sheets impacted by different types of flyers were compared. The nanothermite formed between Al and CuO layers was beneficial to flyer properties. Abstract: Laser-driven flyer technology not only has been widely applied in micro-scale material processing and dynamic high-pressure physics but also possesses obvious advantages in improving the instantaneity and safety of shock initiation. To investigate the launch and impact characteristics between different flyers, six types of typical laser-driven flyers were designed and prepared via magnetron sputtering. The photonic Doppler velocimetry (PDV) and a self-made polyvinylidene fluoride (PVDF) stress sensor were used to collect the velocities and impact stresses of flyers driven by ns-pulsed laser, so that the kinetic energy coupling efficiency and shock initiation property were able to be obtained. Comparisons of characteristics between different flyers were implemented. The effect of nanothermite formed between aluminum and copper oxide layers was verified. The kinetic energy coupling relationship with laser and factors that influenced impact stress of flyers were discussed as well. The results are of significance in optimizing the launch and impact characteristics of laser-driven flyers for practical application.